(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article explores the combined effectiveness of Open AI technologies, particularly ChatGPT, and corpus-based tools such as COCA, Corpora and YouGlish in the field of language learning. As artificial intelligence and authentic language corpora become increasingly integrated into educational settings, their pedagogical potential warrants thorough investigation. This study examines how these tools support language learners in areas such as vocabulary acquisition, pronunciation, grammar, and pragmatic language use. It draws on recent research and case studies to evaluate their usability, accuracy, and motivational impact. Findings suggest that while both AI-driven interaction and corpus-informed exposure significantly enhance learner engagement and understanding, their effectiveness is maximized when used complementarily. The paper concludes with pedagogical recommendations and identifies areas for further research, particularly regarding long-term language retention and the role of human facilitation in AI-supported learning environments.